ANALISIS PENGAWASAN PERSONIL APRON MOVEMENT CONTROL (AMC) TERHADAP FOREIGN OBJECT DEBRIS (FOD) DI APRON BANDAR UDARA INTERNASIONAL YOGYAKARTA - Riska Maya Dessy Antasari; Lady Silk Moonlight; Arnaz Olieve (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Order supervision in the apron of Yogyakarta International Airport conducted by AMC personnel is a very important activity. The increasing number of flights is accompanied by aircraft ground service support equipment which also affects the increasing movement in the apron that will produce Foreign Object Debris (FOD). Then the greater the potential for order violations in the apron. This study to determine the supervision of personnel n the Apron Movement Control on the apron. This quantitative descriptive research method uses the Manual Of Standard CASR - 139 Volume I Aerodrome and SKEP / 100 / XI / 1985 concerning Airport Rules and Regulations. Data collection methods using the method of observation, questionnaires and literature studies. There are still many violations that occur in the apron of Yogyakarta International Airport such as airline employees or airlines and ground heandling that cause Foreign Object Debris (FOD) can have a big impact on aviation safety. This is due to the lack of ramp safety campaigns, personnel and lack of self- awareness from airline or airlines and ground employees.